Simulation-based fleet scheduling in the Metrobus. (2016) - Pekel, Engin; Kara, Selin Soner
A successful fleet scheduling in any public transport system has a prominence. Metrobus is a bus rapid transit (BRT) system in Istanbul and has a high usage percentage among the public transport. The aim of this study is to establish a successful fleet scheduling by using simulation in the Metrobus. In addition, it aims to meet the satisfaction of passengers. Metrobus system is regarded as a discrete system in the study. The distributions of the passengers, which are boarding and disembarking the system, are determined with regard to stochastic process and a discrete-event model is constructed to determine at which bus-stop one boards and disembarks from the Metrobus. A simulation experiment is presented with the results by applying several different scenarios. At least 12.7% decrease in queue for Zincirlikuyu direction and at least 9.9% decrease in queue for Avclar direction is achieved in the developed simulation model. The results prove that simulation-based fleet scheduling can be applied for the Metrobus successfully.